2010
DOI: 10.1155/2010/819687
|View full text |Cite
|
Sign up to set email alerts
|

20 Years of Research on Socioeconomic Inequality and Children's—Unintentional Injuries Understanding the Cause-Specific Evidence at Hand

Abstract: Injuries are one of the major causes of both death and social inequalities in health in children. This paper reviews and reflects on two decades of empirical studies (1990 to 2009) published in the peer-reviewed medical and public health literature on socioeconomic disparities as regards the five main causes of childhood unintentional injuries (i.e., traffic, drowning, poisoning, burns, falls). Studies have been conducted at both area and individual levels, the bulk of which deal with road traffic, burn, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
82
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 68 publications
7
82
1
1
Order By: Relevance
“…The fact that only 4% of the parents were eligible for retirement from a qualified healthcare insurance supported previous reports in the literature stating that burn injuries occur more in families with a low socio-economic and education level (13,14). Although various insurance institutions in Turkey have now been combined under the umbrella of the Social Security Institution, it was important to make this separate grouping to show how many parents had worked in a position that qualified for insurance coverage.…”
Section: Discussionsupporting
confidence: 61%
“…The fact that only 4% of the parents were eligible for retirement from a qualified healthcare insurance supported previous reports in the literature stating that burn injuries occur more in families with a low socio-economic and education level (13,14). Although various insurance institutions in Turkey have now been combined under the umbrella of the Social Security Institution, it was important to make this separate grouping to show how many parents had worked in a position that qualified for insurance coverage.…”
Section: Discussionsupporting
confidence: 61%
“…Some earlier studies have shown that children of asylum seekers are more likely than native children to sustain a burn at a younger age 40. Possibly, in the home, where small children of foreign background spend most of their time, the environment is more detrimental to these young children compared to older children 41 42. The age-specific injury patterns in this study provide an indication of the ages at which different injuries need to be dealt with.…”
Section: Discussionmentioning
confidence: 64%
“…Past policies of colonization and dispossession have led to a cycle of disadvantage, poor education, high unemployment, low income, separation of families and overcrowded living conditions,15 thus contributing to the social and health inequalities in indigenous communities 40 63. Low socioeconomic status increases the risk of childhood injuries,64 and three studies in this review26 30 41 demonstrated its contribution to the higher burden of injuries in indigenous children. The underlying mechanism may be a higher exposure to a wider range of hazards in the living environment, and lack of means of protection 64.…”
Section: Discussionmentioning
confidence: 78%
“…Low socioeconomic status increases the risk of childhood injuries,64 and three studies in this review26 30 41 demonstrated its contribution to the higher burden of injuries in indigenous children. The underlying mechanism may be a higher exposure to a wider range of hazards in the living environment, and lack of means of protection 64. A large proportion of indigenous people live in remote areas, and remoteness, in turn, has been linked with higher rates of injuries 65 66.…”
Section: Discussionmentioning
confidence: 78%